Regulação das apostas no Brasil - Bonfim, Anderson Medeiros (2025)
The operation of lotteries in Brazil has always occurred, at least in the majority, through direct and immediate state exploitation. Furthermore, several lottery activities have always been – and still are – considered illegal. The criminalizing or legalizing reaction is a result of historical comparison, with certain moments experiencing greater disapproval of betting, while at other times we have seen a greater resumption of economic activities related to lotteries. Considering these premises, the first question that arises is regarding the coexistence, in the current model of exploitation, of a model led by Caixa Econômica Federal with another one in formation, this through administrative authorization. It is in this scenario that it is up to regulation to conform the economic power, largely transnational, subjecting them to the constitutional values that determine the protection of health and the soundness of the sources of production and circulation of wealth. In any case, we do not aim to corroborate globally prohibitive practices, nor propose arrangements for self-regulation or deregulation of betting in Brazil. On the contrary, the aim is to highlight the need for mechanisms that preserve individual freedoms, conditioning, to the necessary extent, economic activities based on human vicissitudes, as well as in response to the desires inherent to them